What’s the Fuss about Extra Lessons? Empirical Evidence on Pupils’ Perception - Kingsley Chinaza Nwosu; Emmanuel Chibuike Nwune; Charles Amaechi Anidi; Nnaemeka Kenechi Oguezue (Journal of Research in Education and Pedagogy, 2024)
Divergent perspectives on extra lessons for pupils have dominated current discourse on instructional support. Debates regarding the benefits of extra lessons have been on the increase. A number of experts are of the view that primary school curriculum is overloaded. Often, there is no empirical data for evidence-based policies regarding this. We designed this pilot study to explore students’ extra lessons experiences in order to inform policies. We used a cross-sectional survey design to sample 261 students (male = 54%; female = 46%; mean age = 10.51±1.41) from six intact classes in two primary schools owned and operated by two tertiary institutions in Anambra State. We developed a questionnaire consisting of 9 items to gather students’ views on their extra lessons activities. Part A of the questionnaire comprises the participants’ demographic information while the part B consists of 9 items eliciting the experiences of the participants in extra lessons activities. Major findings demonstrated that the majority of students engaged in extra lessons were satisfied with the lessons, experienced little stress during extra lessons, and learned a lot from them. Furthermore, a higher proportion of male students were more dissatisfied with extra lessons than their female counterparts; and more students reported being dissatisfied with the extra lessons when they lasted longer than two hours per day. The implications of the findings were highlighted, and it was concluded that, while extra lessons may benefit primary school pupils, if not properly implemented, they may be detrimental to students’ mental health and learning outcomes.